Perceived holistic benefits of equine-assisted therapy among mothers of children with a disability: a pilot study - Escobar, Melody (Journal of spirituality in mental health, 2021)
This paper presents the first phenomenological qualitative descriptive study exploring the connection between spirituality and equine therapy. Results highlight experiences of 17 mothers with children with disabilities who participated in a 12-week session from January to May 2018 at a Texas equine center. Themes included mothers’ perceptions of spirituality as a supporting force, disability and social isolation affecting child and mother, and equine therapy as a holistic intervention. This pilot study followed Max van Manen’s methodological structure of human science inquiry. Findings demonstrated the challenges of caring for children with disabilities and the potential adverse impact to caregivers’ health.